Of Stag Hunts and secret societies: Cooperation, male coalitions and the origins of multiplicity. (September 2022) - Lees, Nicholas
In many circumstances where multiple, autonomous actors exist, cooperation is only a viable strategy if other actors also pursue a strategy of cooperation. Such situations can be characterised in terms of the Stag Hunt, based on a parable told by Rousseau. Although traditionally interpreted as a device for understanding how mutually beneficial cooperation can emerge, Harrison Wagner points out that would-be exploiters must overcome similar problems to succeed at subjugating others. Successful cooperation may have the ironic consequence of enabling deeper conflict within and between a multiplicity of societies. Despite its canonical status, the importance of the Stag Hunt for understanding the interaction between multiple societies may have been underestimated. Nonetheless, rational choice theory alone cannot explain how cooperation-for-predation became established, while historical sociology's conventional 'materialist metanarrative' of the origin of war and the state may have unduly neglected the role of gender relations. The phenomenon of men's secret societies, found in many stateless societies, indicates that fraternal solidarity within coalitions of men competing to control women's labour and bodies may provide a path to the nucleation of warlike states. If this is correct, it becomes clear that in many societies, men and women experience multiplicity in qualitatively different ways.